The Two-Step P2P Simulation Approach - Hannes Birck; Oliver Heckmann; Andreas Mauthe; Ralf Steinmetz (Journal of Communications Software and Systems, 2005)
In this article a framework is introduced that can be used to analyse the effects & requirements of P2P applications onapplication and on network layer. P2P applications are complex and deployed on a large scale, pure packet level simulations do not scale well enough to analyse P2P applications in a large network with thousands of peers. It is also difficult to assess the effect of application level behavior on the communication system. We therefore propose an approach starting with a more abstract and therefore scalable application level simulation. For the application layer a specific simulation framework wasdeveloped. The results of the application layer simulations plus some estimated background traffic are fed into a packet layer simulator like NS2 (or our lab testbed) in a second step to perform some detailed packet layer analysis such as loss and delay measurements. This can be done for a subnetwork of the original network to avoid scalability problems.